Penerapan Puspaga dalam Pencegahan Kekerasan pada Anak di Kelurahan Sidosermo, Kecamatan Wonocolo, Kota Surabaya - Bayu Daffario Ardana; Singgih Manggalou (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to find out how PUSPAGA is implemented to stop violence against children. Sidosermo Village is located in Wonocolo sub-district, Surabaya, Indonesia. The village is known for its PUSPAGA program, which is held in every RW Hall. This research uses a qualitative approach with descriptive methods. Based on the study, this research has referred to the public policy implementation model according to Van Metter and Van Horn, fulfilling six variables. During the PUSPAGA implementation program in Sidosermo Village, effective communication occurred between the various organizations involved, making it easier to coordinate interrelated activities throughout the implementation process. The Surabaya Department of Child Empowerment and Protection and Population Control and Family Planning (DP5A) and PUSPAGA collaborate with various departments and institutions according to the community's needs.